Fluoroless ablation of atrial fibrillation using intracardiac ultrasound integrated with 3D electroanatomical mapping system. (24th May 2021) - Antolic, B; Jan, M; Vrbajnscak, M; Zizek, D; Kajdic, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Intracardiac echocardiography (ICE) is gaining increasingly wider adoption in interventional electrophysiology (EP) and represents an all-round tool for ablation of atrial fibrillation (AF). The key upgrade to the usefulness of ICE is its integration into three-dimensional (3D) electroanatomic mapping (EAM) system (ICE/EAM automatic integration system). Purpose: The aim of this single-centre retrospective study was to evaluate feasibility, safety and acute efficacy of ICE/EAM automatic integration system guided fluoroless ablation of AF.  Methods: Patients with symptomatic paroxysmal or persistent AF referred for first pulmonary vein isolation (PVI) radiofrequency catheter ablation (RFCA) from September 2017 to August 2020 were included in the study. Those who underwent additional ablations for concomitant arrhythmias were excluded from statistical analysis. All procedures were performed without the use of fluoroscopy. A detailed 3D virtual anatomy of the left atrium (LA) and structures relevant to AF ablation was constructed from ultrasound contours obtained with ICE probe inside the LA. Pulmonary veins (PVs) and antral regions were additionally mapped with fast anatomical mapping. PVI was performed with contact force (CF) sensing catheter. Procedural endpoint was successful PVI.  Results: A total of 56 patients underwent RFCA (35.7% females, median age 62.7 years, 53.6% paroxysmal AF). Acute PVI was achieved in all patients (100%). Adverse events were detected in two patients (3.6%). The median procedure duration was 110.5 min (IQR 100.0-133.8). First-pass isolation was achieved in 50/56 LPVs (89.3%) and in 44/56 RPVs (78.6%). In patients where first-pass isolation was no achieved, intravenous carina had to be ablated in 3/6 (50%) of LPVs and 9/12 (75%) of RPVs.  Conclusions: Flouroless PVI using ICE/EAM automatic integration system is feasible, safe and acutely effective. We achieved high rate of first-pass isolation.